p53, PTEN Tumor Suppressor Gene Methylation in Thyroid Cancer - FAWZI AHMED, GHAZWAN; SALIM PITY, INTISAR; MUHAMMAD, AHMAD (Al-Kufa University Journal for Biology, 2019)
Background and objective: DNA methylation serves as an alternative to the mutational inactivation due to epigenetic event that alters gene expression without changing its DNA sequence. Such alterations may silence putative DNA repair genes and tumor suppressor genes whose role is undisputed in malignant transformation. This study was performed to detect the frequency of p53 and PTEN methylation in different thyroid cancers. Method: Using methylation specific PCR methods, DNA was extracted from 76 surgically resected thyroid tissues with primary cancer. The target (p53, PTEN tumor suppressor genes) DNA was amplified with the mutation-specific primers. Results: p53 gene complete methylation and partial methylation were 13.2%, and 17.1% respectively, whereas PTEN complete methylation and partial methylation were 18.4% and 23.7% respectively. Complete p53 methylation was significantly frequent among Anaplastic thyroid cancer (ATC) cases (50.0%) compared with other thyroid cancer, followed by Follicular thyroid cancer (FTC) (33.3%). Papillary carcinoma cases were more likely to be unmethylated for p53 gene. Despite the trend of negatively associated PTEN complete methylation with any of the studied clinicopathological parameters, however, merging partial with complete methylation gave a significant association of PTEN methylation with FTC and, inversely, there was low link with Papillary thyroid cancer (PTC). Conclusion: Combined silencing of PTEN and p53 faithfully reproduces the development of ATC, and may provide a compelling rationale for a future target chemotherapy. p53 methylation appears low among early staged (T1, T2 and N0) tumors may indicate that p53 silencing is a hallmark of advanced tumors and so has bad ominous sign. PTEN methylation is also significantly associated with follicular carcinoma whereas, inversely, low in papillary carcinoma.